Non-destructive evaluation of wire arc additively manufactured samples with surface roughness - Wee, Adwin Hong Shiun (Nanyang Technological University, 2024)
Wire Arc Additive Manufacturing (WAAM) is a type of Metal Additive Manufacturing (MAM) method that uses welding technology to fabricate 3D components. It is a cost-effective method to producing large metallic components due to its high deposition rate. During fabrication, defects such as delamination and cracks may be introduced on the surface or within the component. Such defects affect the performance of the components. As such, inspection of the fabricated components is necessary. Non-Destructive Evaluation (NDE) methods, namely Ultrasonic Testing (UT), can be used to detect the defects. However, there is a lack of inspection guidelines related to WAAM. Thus, there is a need to study UT on WAAM components to promote WAAM adoption in the industry.